Ultra-fine metal particles dispersed on single-walled carbon nanotubes for energy devices - Ishii, Yosuke; Ishikawa, Sae; Yamada, Itta; Kondo, Kohei; Jindo, Shinya; Kawasaki, Shinji; Hattori, Yoshiyuki; Mashkov, Oleksandr; Heiß, Wolfgang (Journal of Materials Science, 2022)
We prepared metal nano-particles deposited on SWCNTs by heat-treatment of SWCNTs encapsulating metal complex (Ni(acac)2, Cu(acac)2) molecules inside their hollow cores. It was confirmed by synchrotron radiation x-ray absorption spectra that the obtained nano-particles were metallic Ni and Cu. Electron microscopic measurements revealed that the diameters of most of the metal particles are less than 10 nm and that they were well dispersed on SWCNTs even in the bundles. Ni metal particles on SWCNTs were converted to Ni(OH)2 particles by electrochemical treatment in 1 M KOH aqueous solution. We investigated the Ni-MH battery electrode properties of the obtained Ni(OH)2/SWCNT sample. We expect Ni(OH)2/SWCNT to work as high-power battery electrode, because the reversible charge/discharge capacity of Ni(OH)2/SWCNT did not change much with increasing the scan rate from 2 to 1000 mV/s. Cu/SWCNT worked as a CO2 photo-reduction catalyst by combing it with light-absorbing semiconductors. In the photo-catalyst, Cu works as a metal co-catalyst to enhance the reaction efficiency. We used inorganic semiconductor TiO2 and organic semiconductor epindolidine (EPI). It was found that both Cu/SWCNT/TiO2 and Cu/SWCNT/EPI can work as CO2 photo-reduction catalyst. The external CO2 to CO quantum yield of Cu/SWCNT/EPI catalyst under the simulated solar light (AM1.5G, 100 mW/cm2) was 2.2 × 10−4%. Graphical abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-02-04